2006
DOI: 10.1038/sj.bjc.6603354
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor substrates mediate distinct biological responses to insulin-like growth factor receptor activation in breast cancer cells

Abstract: Activation of the type I insulin-like growth factor receptor (IGF-IR) regulates several aspects of the malignant phenotype, including cancer cell proliferation and metastasis. Phosphorylation of adaptor proteins downstream of IGF-IR may couple IGF action to specific cancer phenotypes. In this study, we sought to determine if insulin receptor substrate-1 and -2 (IRS-1 and -2) mediate distinct biological effects in breast cancer cells. Insulin receptor substrate-1 and IRS-2 were expressed in T47D-YA breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 46 publications
4
110
0
1
Order By: Relevance
“…1C and S1) (5). IRS-1 is a key mediator of IGF-1-dependent breast cancer cell proliferation (17). We reasoned that cells expressing K388R PR-B should be more responsive to IGF-1 due to PR-dependent elevated IRS-1 expression.…”
Section: Hormone-independent Pr Target Genes Contribute To Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…1C and S1) (5). IRS-1 is a key mediator of IGF-1-dependent breast cancer cell proliferation (17). We reasoned that cells expressing K388R PR-B should be more responsive to IGF-1 due to PR-dependent elevated IRS-1 expression.…”
Section: Hormone-independent Pr Target Genes Contribute To Breast Cancermentioning
confidence: 99%
“…The transcription of IRS-1 is PR-B driven and requires Ser-294 phosphorylation, but also occurs in the absence of progestins (3). IRS-1 is an adaptor molecule in the IGF receptor pathway that is critical for IGF-1 mediated proliferation of breast cancer cells (17). We therefore tested whether IRS-1 expression was sensitive to PR sumoylation using real-time PCR in T47D cells stably expressing either wt, S294A or K388R PR-B.…”
Section: Sumoylation Of Pr-b Represses Transcription Of a Subset Of Tmentioning
confidence: 99%
“…The identification of such biomarkers remains arguably the most important issue in development of drugs targeting IGF-IR. Previous studies have reported on the expression of IGF1-R, phospho-IGF-IR, insulin receptor substrates-1 (IRS1), and -2 (IRS2), and predictive gene expression signatures (10)(11)(12)(13). This report describes a detailed assessment of certain elements of the pathway, including an evaluation of the receptor and its ligands, and its proximal and distal signaling proteins with expression array profiles, focusing exclusively on breast and colorectal cancer (CRC) models.…”
mentioning
confidence: 99%
“…There have been reports that delta-PHPTB IRS-2 may have biological activity [16,17] . The delta-PHPTB IRS-2 is fully capable (as is wild type IRS-2 and IRS-1) of both stimulating growth and inhibiting differentiation of 32D-IGF-1R cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IRS-1 proteins lacking the same PH and PTB domains are completely inactive in blocking differentiation and stimulating IL-3-independent growth of 32D-IGF-1R cells [6] . Down-regulation of IRS-2 may affect the protein's nuclear functions, bypassing its conventional signaling pathway [17,18] .…”
Section: Discussionmentioning
confidence: 99%